2015
DOI: 10.1159/000439227
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Targeted Treatment Improves Cognitive Function in Patients with Precapillary Pulmonary Hypertension

Abstract: Background: Patients with pulmonary hypertension (PH) may suffer from cognitive deficits that potentially relate to reduced oxygen delivery and cerebral tissue oxygenation (CTO). Objective: To evaluate the hypothesis that cognitive function improves with therapy, along with improved CTO. Methods: Twenty incident patients with arterial or chronic thromboembolic PH had CTO monitoring by near-infrared spectroscopy during diagnostic right heart catheterization. Cognitive tests [Trail Making Tests (TMTs), Victoria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
(58 reference statements)
1
8
1
Order By: Relevance
“…Guillevin et al reported various social challenges in the PAH group, such as difficulties in maintaining social relationships, significant financial problems, as well as mood lability 31 . We found significant cognitive impairment in PAH patients, especially in delayed recall, consistent with previous studies 7,32 . Multiple conditions with chronic disorders demonstrated loss of white and GM volume and tissue integrity 12,15,16,19,20,22 .…”
Section: Discussionsupporting
confidence: 88%
“…Guillevin et al reported various social challenges in the PAH group, such as difficulties in maintaining social relationships, significant financial problems, as well as mood lability 31 . We found significant cognitive impairment in PAH patients, especially in delayed recall, consistent with previous studies 7,32 . Multiple conditions with chronic disorders demonstrated loss of white and GM volume and tissue integrity 12,15,16,19,20,22 .…”
Section: Discussionsupporting
confidence: 88%
“…We have shown previously that cerebral tissue oxygenation is correlated to cognitive performance in PAH/ CTEPH patients [8], and that a lower cerebral tissue oxygenation during exercise is prevented with oxygen therapy [4,18]. Thus, by improving systemic and possibly cerebral oxygenation DOXT may have enhanced cerebral functions (table 3).…”
Section: Discussionmentioning
confidence: 94%
“…Mean nocturnal SpO 2 , oxygen desaturation index (ODI: number of SpO 2 dips ⩾4% lasting ⩾10 s•h −1 ), pulse rate and apnoea-hypopnoea index (AHI: number of apnoeas + hypopnoeas per hour with reduction of breathing amplitude <50% of baseline lasting ⩾10 s and associated with a SpO 2 dip ⩾4%) were determined [17]. Cognitive performance was tested using the Stroop test [18].…”
Section: Assessmentsmentioning
confidence: 99%
“…Earlier reports indicate that though PDE4C is expressed in the brain, limited to the cortex, thalamic nuclei and cerebellum 81 . No evidence currently exists to show if activating PDE4C plays a conclusive role in rescuing cognitive deficits 89 .…”
Section: Discussionmentioning
confidence: 99%